Antioxidant Activity of Rhodomyrtus tomentosa (Kemunting) Fruits and Its Effect on Lipid Profile in Induced-cholesterol New Zealand White Rabbits - Muhamad Fahrin Maskam; Jamaludin Mohamad; Mahmood Ameen Abdulla; Adlin Afzan; Isa Wasiman (Universiti Kebangsaan Malaysia, 2014)
The objective of this study was to determine the antioxidant activity of Rhodomyrtus tomentosa fruit extract and its effect on triacylglycerides (TG), total cholesterol (TC), low density lipoprotein (LDL), high density lipoprotein (HDL) and lipid peroxidation in induced-cholesterol New Zealand White Rabbits. In DPPH assay, at concentration of 200 ug/mL methanol extract give 62.13% inhibition of DPPH free radicals with IC50 of 107 μg/mL. Similarly, in FRAP assay the methanol extract at concentration of 500 ug/mL showed the highest absorbance (0.16) for antioxidant activity. Whereas, in metal chelating assay the methanol extract at concentration of 100 mg/mL exhibited 36% inhibition of metal chelating ions. The antioxidant activities were due to the presence of phenolics compounds of quinic acid, gallic acid and caffeic acid, which were identified with Q-TQF MS. Total phenolic and total flavonoid content was the highest in water extract at 66.515 mg of GAE/g and 1.828 mg of QE/g, respectively. The water extract of R. tomentosa was non-toxic at LC50 = 616.083 μg/mL. The white New Zealand rabbits group A was fed by oral gavages with normal diet; Group B cholesterol 1% diet; group C cholesterol 1% diet with fruit extract 50 mg/kg and Group D cholesterol 1% diet with simvastatin standard drug 5 mg/kg. The rabbits in group C has a significantly reduced (p<0.05) total cholesterol (TC), low density lipoprotein (LDL) and significantly increased (p<0.05) high density lipoprotein (HDL) and triacylglycerides (TG) as compared with group B. The lipid peroxidation was reduced significantly (p<0.05) as indicated by the low TBARs-MDA level in group C. Thus, these results showed that the R. tomentosa fruit extracts was able to reduce cholesterol level and increased HDL level which can prevent the formation of atherosclerosis in New Zealand white rabbits.